ASYMMETRIC NEXUS OF EXPORT, EXCHANGE RATE, FDI, AND ECONOMIC DEVELOPMENT IN INDONESIA - Lutfiatul Azizah; Aminudin Ma'ruf (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study examines whether exports, exchange rates, and foreign direct investment respond asymmetrically to positive and negative shocks in Indonesia's gross domestic product (GDP) over the period 1973 to 2022, using the Nonlinear Autoregressive Distributed Lag (NARDL) model. We estimate three different models where exports, exchange rate and FDI are used as dependent variables with GDP as the key explanatory variable. The results suggest asymmetric responses in two of the three models. In the case of exports, positive GDP shocks are associated with a significant positive response in exports, whereas negative shocks have an insignificant impact, suggesting that export commodity dependence in Indonesia is not vulnerable to domestic recessions. For FDI, positive GDP growth attracts long-run investment inflows while economic contractions produce a modest but significant negative effect, consistent with threshold-based investor behaviour. For the exchange rate, both positive and negative GDP shocks are insignificant, implying that exchange rate movements are largely influenced by monetary and capital movements, rather than output. The results are consistent with the use of asymmetric modelling for the Indonesian macroeconomy, as positive and negative GDP shocks produce markedly different responses across the three models, with implications for growth-enhancing policies that account for the non-linearity of macroeconomic transmission.